Languange function found in mulan movie - Wahyuni, Ni Kadek Dian; Ariyaningsih, Ni Nyoman Deni; Jendra, I Made Iwan Indrawan (Journal of Language and Applied Linguistics, 2021)
The data source was taken from conversation among the characters in Mulan movie. The data was collected by using observation method based on library research. There were some steps in collecting the data. The qualitative method was the method that was used in analysing the data in this study. The conversation among the characters analysed in the category types of language function that was according to the book written by Blundell (1987) entitled Function in English. The data was presented by the formal method which presented the language function. The research finding showed that there are four type of Language Function: main function, social formula, making communication work and finding out about language. Based on the data, there are 33 data for main function, 15 data for social formulas and 2 data for making communication work. The study concluded that the most used language function was main function and the least used language function was finding out about language